2018
DOI: 10.1590/1678-4162-10158
|View full text |Cite
|
Sign up to set email alerts
|

Use of EDTA in the treatment of local tissue damage caused by the Bothrops alternatus venom

Abstract: Twelve adult rabbits were distributed in three groups and received on the femoral biceps region, via intradermal injection (ID), 25µg of Bothrops alternatus venom dissolved in NaCl 0.9% and diluted in 0.25mL of phosphate buffered saline (PBS). Thirty minutes later, the group G1 received 0.25mL of phosphate buffered saline (PBS) ID while to G2 and G3 25mg of ethylenediamine tetraacetic acid (EDTA) dissolved in 0.25mL of PBS were administered via intramuscular (IM) and intravenous (IV) injection, respectively. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…It is known that several snake venom enzymes are particularly dependent on Ca 2+ , Mg 2+ , and Zn 2+ metal ions [29] and particularly dependent on divalent metal ions, including Ca 2+ -dependent phospholipase A2, divalent metal ion-dependent 5'-nucleotidase, Mg 2+ -dependent phosphodiesterase, Mg 2+or Ca 2+ -dependent alkaline phosphatase, and Zn 2+ -dependent proteinase [28,30,31]. Some metalloproteinases that present Zn 2+ ions in their structures are responsible for proteolytic degradation of the extracellular matrix, inflammations, hemorrhages, and other physiological responses [32][33][34]. Therefore, our metalloproteomics data corroborate the literature for presenting the highest levels of Ca 2+ and Zn 2+ ions and metalloproteinases in the Bothrops and L. m. muta venoms in relation to C.d.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that several snake venom enzymes are particularly dependent on Ca 2+ , Mg 2+ , and Zn 2+ metal ions [29] and particularly dependent on divalent metal ions, including Ca 2+ -dependent phospholipase A2, divalent metal ion-dependent 5'-nucleotidase, Mg 2+ -dependent phosphodiesterase, Mg 2+or Ca 2+ -dependent alkaline phosphatase, and Zn 2+ -dependent proteinase [28,30,31]. Some metalloproteinases that present Zn 2+ ions in their structures are responsible for proteolytic degradation of the extracellular matrix, inflammations, hemorrhages, and other physiological responses [32][33][34]. Therefore, our metalloproteomics data corroborate the literature for presenting the highest levels of Ca 2+ and Zn 2+ ions and metalloproteinases in the Bothrops and L. m. muta venoms in relation to C.d.…”
Section: Discussionmentioning
confidence: 99%
“…Because SVMPs require a divalent cation such as zinc for activity, the use of metal chelating agents such as CaNa 2 EDTA( Flowers and Goucher, 1963 , 1965 ; Gowda et al, 2011 ; Howes et al, 2007 ; León et al, 1998 ; Rucavado et al, 2000 ; Silva-Neto et al, 2018 ), tetraethyl thiuram disulfide (Disulfiram/TTD)( Nanjaraj Urs et al, 2015 ; Rudresha et al, 2021 ), 2,3-dimercapto-1-propanesulfonic acid (DMPS/Unithiol)( Albulescu et al, 2020a ; Menzies et al, 2022 ; Xie et al, 2020a ), and dimercaprol (British anti-Lewisite) ( Albulescu et al, 2020b ; Xie et al, 2020b ) for SBE therapy has been demonstrated in a variety of animal models. These agents have traditionally been used to treat metal intoxication( Flora and Pachauri, 2010 ), but have found a use as repurposed drugs for SBE therapy.…”
Section: Adjunctive Field-based Therapies For Pre-hospital Management...mentioning
confidence: 99%
“…Além disso, as alterações vasculares proeminentes que levam a hemorragia e edema podem contribuir para isquemia e necrose tecidual adicional Silva-Neto et al,2018).…”
Section: Metaloproteasesunclassified